Extent Of Balanced Scorecard Measures Usage In Relationship With Organization Size And Market Factors: Impact On Organization Performance - Lim, Chin Joo (2002)
This research was conducted to study the relationship between the balanced scorecard usage in relationship with organization size, product life cycle stage and market strength position. It was also intended to study the impact of balance scorecard usage on organization performance. Based on information collected from 86 manufacturing companies operating in the Northern States of Malaysia, the results of the research suggest that organization size and businesses with early product life cycle stage use more balanced scorecard measures.